2009
DOI: 10.2174/1874836800903010042
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cast-In-Place Concrete and Precast Concrete Blocks Incorporating Waste Glass Powder

Abstract: This paper deals with studies on the use of waste glass powder as an effective ingredient in concrete. Studies on cement pastes including mechanical property tests and thermal analysis were used to understand the influence of the glass powder on the cement hydration process and to arrive at an optimal dosage range. Cast-in-place concrete and block mixtures were proportioned with varying dosages of glass powder, and tests for mechanical properties, alkali-silica reaction, and water absorption were carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, in the last couple of decades, concrete production and construction methods have been improved significantly due to the availability of modern technologies [1,2]. Concrete construction has shifted from the conventional practice of in-situ method to the pre-cast method [3]. Very recently, 3D printing of concrete is being advanced rather than the conventional practice of casting concrete into formwork [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last couple of decades, concrete production and construction methods have been improved significantly due to the availability of modern technologies [1,2]. Concrete construction has shifted from the conventional practice of in-situ method to the pre-cast method [3]. Very recently, 3D printing of concrete is being advanced rather than the conventional practice of casting concrete into formwork [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that GPK "fuel" shells is finer than cement, and this may be as a result of the fact that the shape of the particles in the GPK "fuel" shells were observed to be elongated. This line of thinking is similar to that reported by [33] when glass powder was used as partial replacement for cement. However, the fineness value of the GPK ordinary shells fell far below the typical ordinary Portland cement specific surface.…”
Section: Determination Of Flexural Strengthsupporting
confidence: 87%
“…A large number of studies have been carried out to assess the pozzolanic reactivity of glass powder, obtained by grinding bottled glass, in concrete when used as partial replacement of cement [6][7][8][9][10][11][12][13][14]. A study by Shi et al showed that the strength activity index for mortars prepared with glass powder having an average size of 100 microns is approximately 74% [6].…”
Section: Previous Research On the Use Of Recycled Glass In Concretementioning
confidence: 99%